Endovascular Treatment and Outcomes for Femoropopliteal In-Stent Restenosis: Insights from the XLPAD Registry. (15th July 2022) - Vu, Michael H.; Sande-Docor, Glaiza-Mae; Liu, Yulun; Tsai, Shirling; Patel, Mitul; Metzger, Chris; Shishehbor, Mehdi H.; Brilakis, Emmanouil S.; Shammas, Nicolas W.; Monteleone, Peter; Banerjee, Subhash
Abstract : Background . There is limited "real-world" evidence examining treatment modalities and outcomes in patients with symptomatic peripheral arterial disease undergoing endovascular treatment of femoropopliteal (FP) in-stent restenosis (ISR). Materials and Methods . We compared outcomes in 2, 895 patients from the XLPAD registry (NCT01904851) between 2006 and 2019 treated for FP ISR ( n = 347) and non-ISR ( n = 2, 548) lesions. Primary endpoint included major adverse limb events (MALE) at 1 year, a composite of all-cause death, target limb repeat revascularization, or major amputation. Results . ISR patients were more frequently on antiplatelet (94.5% vs 89.4%, p = 0.007 ) and statin (68.9% vs 60.3%, p = 0.003 ) therapies. Lesion length was similar (ISR: 145 ± 99 mm vs. non-ISR: 142 ± 99 mm, p = 0.55 ). Fewer treated ISR lesions were chronic total occlusions (47.3% vs. 53.7%, p = 0.02 ) and severely calcified (22.4% vs. 44.7%, p < 0.001 ). Atherectomy (63.5% vs. 45.0%, p < 0.001 ) and drug-coated balloons (DCB; 4.7% vs. 1.7%, p < 0.001 ) were more frequently used in ISR lesions. The distal embolization rate was higher in ISR lesions (2.4% vs. 0.9%, p = 0.02 ). Repeat revascularization (21.5% vs. 16.7%, p = 0.04 ; Figure) was higher and freedom from MALE at 1 year was significantly lower (87% vs. 92.5%, p < 0.001 ) in the ISR group. Conclusion . Atherectomy and DCB are more frequently used to treat FP ISR lesions. Patients with FP ISR have more intraprocedural distal embolization, higher repeat revascularization procedures, and lower freedom from MALE at 1 year.